ANALISIS AKTIVITAS ANTIBAKTERI SEDIAAN GEL EKSTRAK ETANOL 70% DAUN KEMANGI (Ocimum americanumL.) TERHADAP BAKTERI Propionibacterium acnes - Triyani Sumiati; Eem Masaenah; Lydia Asriyani (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2019)
Acne is skin disease caused due to a blockage of the oil gland channel and infection by the bacteria Propionibacterium acnes. Ethanol extract of 70% basil leaves has been known to be potent as antibacterial to Propionibacterium acnes. This study aims to determine the physical quality of gel preparation and antibacterial activity analysis of gel ethanol extract preparation of 70% basil leaves (Ocimum americanum L.) to Propionibacterium acnes bacteria. In this research, ethanol extract 70% of basil leaf is formulated into gel preparation form with various concentration of extract that is 45%, 55%, and 55% then in physical quality test include: organoleptic test, pH, spreading, and viscosity. The gel preparation was then analysed for its antibacterial activity using the diffusion method for the wells. Based on ethanol extract research, 70% of basil leaves had antibacterial activity with drag zone diameter of 5,20 mm (45% extract concentration), 6,06 mm (concentration of extract 50%) and 7,13 mm (concentration of extract 55%). In this study can be concluded that the higher concentration of ethanol extract 70% basil leaves the higher the inhibit zone diameter.